PERAN SERVICESCAPE DALAM MENINGKATKAN HOTEL IMAGE DAN REVISITING INTENTION PADA HOTEL BINTANG 5 - Fadia Ayunisa (Jurnal Manajemen dan Pemasaran Jasa, 2016)
The purpose of the research is to analyze the influences of social servicescape and physical servicescape on hotel image and revisiting intention in five star hotels. The design of this study is a hypothesis testing. The respondents were selected using purposive sampling method in which the questionnaires are used to collect data from 200 respondents who have visited some five star hotels in DKI Jakarta at least 1 time in a year. The proposed model was tested by using Structural Equation Model (SEM). The results of this research showed that there is a significant and positive influence of social servicescape and physical servicescape on hotel image; a significant and positive influence of hotel image, social servicescape and physical servicescape on revisiting intention. This study only used some five star hotels in DKI Jakarta and 200 respondents that limit the generalizability of the results. Future researchers should accomodate larger number of respondents and used some other Five Star Hotels in other cities. The findings of this research can help hotel managers to implement better strategies in order to increase the level of customers’ revisiting intention.